The historic garden heritage of Central and Eastern Europe and new challenges for landscape architecture - Van Den Toorn, Martin (4D Journal of Landscape Architecture and Garden Art, 2018)
In this paper I will put forward some aspects of the position Central and Eastern Europe in the European history of landscape architecture, with a special focus on Hungary. The key question is how this position influences the contemporary planning and design of landscapes where heritage plays a role.The first part of the paper will pay attention to the historical development of the garden as a landscape element in the history of landscape architecture in general and how it affected thinking and practice. It will be further elaborated on the position of Central and Eastern Europe in the context of European landscape architecture and the special position of Hungary.The second part deals with the design approaches related to heritage and contemporary planning and design of landscapes. These design approaches will be placed in the frame or the new challenges for landscape architecture for the future; water conservation, energy transition and the creation of comfort and healthy environments for people. It will be worked out in a case study in Romania; the landscape of the Maros river valley.In the conclusions the concept of 'readability' is put forward in the context of heritage in landscape architecture as an alternative for conservation.
Keywords: historicism; readability; design approach; design experiment; design knowledge